FEATURES OF INFORMATION SECURITY IN MARTIAL LAW - Moroz, Viktor (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the article is devoted to the analyze of the features of information security in martial law. Research methods: comparative analysis of individual regulations and the case law of Ukraine regulatory framework and case law in the application of the information security in martial law. Results: normative regulation of the formation of a single information space in Ukraine should contribute to the harmonious development of information resources, information services and the information product in the country. Improving the effectiveness of the subjects under investigation countering threats to information security. Discussion: the analysis of the legal the features of information security in martial law is carried out.